Physicians` Knowledge Regarding Nutritional Management in Children with Diarrhea: a Study in Kerman, Iran (I.R.) - Amini-Ranjbar, Seddiqe; Bavafa, Babak (Pakistan Journal of Nutrition, 2007)
Acute diarrhea is one of the common causes of malnutrition and mortality in children younger than 5 years of age, especially in developing countries. The high prevalence of malnutrition in Kerman, the largest province of Iran, in addition to the importance of physicians` awareness in the dietary management of children with acute diarrhea encouraged us to identify the knowledge of a group of physicians, regarding the nutritional management of children with diarrhea. This research was conducted on 122 pediatricians and general practitioners in 2005. They obtained a mean (±SD) total score of 14 (±3.4) out of 22 (the maximum achievable score). The knowledge score according to sex and years of working experience of the physicians showed significant difference. Not only none of the physicians believed in omitting breast-feeding, but also 64.8% of the respondents recommended increasing breast-feeding. Although diluted formula was advised by 42.5%, but lactose free formula was only prescribed in 6%. Majority (95.1) of respondents prescribed ORS. In conclusion the study highlighted a gap in knowledge of physicians as the core subjects in the nutrition education and dietary management of acute episodes of childhood diarrhea.